The efforets of limam alraazi (t;666 hu) Exblanatory in his dictionary Mukhtar AL-lsihah ( Surah AL-kahf as a model ) (Journal of the College of Basic Education, 2023)
In our tagged search (The efforts of Imam AlRrazi(t-666hu)Explanatory in mukhtar al-sahah) and we set aside It (surat aI-Baqarah as amodel)which we based on two chapters it was the first chapter for to introduce the personality of Imam Muhammad bin abi Bakr bin Abdl Qadir Al-razi and Mukhtar al-Sihahs . We devoted two topics to this great personality, and a third topic for Mukhtar Al-Sahahs In the first study we presented his autobiography which was represented by his name lineage and nickname birth and death, As for the second topic we dealt with his scientific biography the scientisits and their seventh scientists were represented .As for the third topic ,in which we dealt with the definition, the lexicon of Mukhtar Al-Sahah it is one of the most famous works of AI-Razi then we included the methodology that AI-Razi followed when he shortened it to Al-sahah. Then we went back to the second chapter explaining theexegetical efforts of Imam Al-Razi in the lexicon of Muktar AI-Sahah which includes in it the Quranic evidence coupled with the explanatory material takefrom alarge number of interpetations,Aswell as the linguistic material that has been attributed to the Quranic witness, along with the readings that were mentioned in some articles of the dictionary,The search was concluded by the grace of God Almight .